2015
DOI: 10.1371/journal.pone.0138048
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Subcutaneous Administration of Oxytocin Accelerates Angiotensin II-Induced Hypertension and Renal Damage in Male Rats

Abstract: Oxytocin and its receptor are synthesised in the heart and blood vessels but effects of chronic activation of this peripheral oxytocinergic system on cardiovascular function are not known. In acute studies, systemic administration of low dose oxytocin exerted a protective, preconditioning effect in experimental models of myocardial ischemia and infarction. In this study, we investigated the effects of chronic administration of low dose oxytocin following angiotensin II-induced hypertension, cardiac hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…This lack of effect is consistent with a recent study demonstrating that prolonged s.c. administration of OXT (20–100 ng/kg/h, 28 days) exerts no changes on heart rate or blood pressure in rats . The same study also reported that prolonged administration of OXT did not change plasma concentrations of atrial natriuretic peptide and renin, nor plasma osmolality . Consistently, plasma osmolality and sodium concentrations were also found to be unaffected by chronic intranasal OXT treatment in our experimental clinical settings.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This lack of effect is consistent with a recent study demonstrating that prolonged s.c. administration of OXT (20–100 ng/kg/h, 28 days) exerts no changes on heart rate or blood pressure in rats . The same study also reported that prolonged administration of OXT did not change plasma concentrations of atrial natriuretic peptide and renin, nor plasma osmolality . Consistently, plasma osmolality and sodium concentrations were also found to be unaffected by chronic intranasal OXT treatment in our experimental clinical settings.…”
Section: Discussionsupporting
confidence: 78%
“…Because no previous studies had reported on blood pressure effects of chronic OXT administration in humans, we showed for the first time that the mean systolic pressure values remained unaltered after 4 months of OXT treatment in a group of normotensive patients with schizophrenia. This lack of effect is consistent with a recent study demonstrating that prolonged s.c. administration of OXT (20-100 ng/kg/h, 28 days) exerts no changes on heart rate or blood pressure in rats (38). The same study also reported that prolonged administration of OXT did not change plasma concentrations of atrial natriuretic peptide and renin, nor plasma osmolality (38).…”
Section: Discussionmentioning
confidence: 86%
“…We now studied both sexes in the context of ANGII infusion, diabetes, and ACE2 deficiency, and focused our approach on kidney function and histopathology. It is accepted that ANGII promotes cardiac hypertrophy, hypertension, albuminuria, GFR decrease, and tubular injury [55][56][57][58][59]. Here we report a sex dimorphism on these effects.…”
Section: Discussionsupporting
confidence: 53%
“…We would thus expect that AVP signaling is detrimental in this context, and OT is favorable. However this statement may not be accurate in view of the recent study by Phie et al [ 32 ]. They demonstrated that in the rat model of Ang II-induced hypertension, chronic co-treatment with OT failed to prevent the increase of blood pressure and LV hypertrophy.…”
Section: Ot and Cardioprotectionmentioning
confidence: 90%